2020
DOI: 10.1002/cssc.202001216
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Mechanism of Rechargeable Aqueous Zn–MnO2 Batteries: Implementation of Charging Process by Electrodeposition of MnO2

Abstract: Poor cycling stability and mechanistic controversies have hindered the wider application of rechargeable aqueous Zn–MnO2 batteries. Herein, direct evidence was provided of the importance of Mn2+ in this type of battery by using a bespoke cell. Without pre‐addition of Mn2+, the cell exhibited an abnormal discharge–charge profile, meaning it functioned as a primary battery. By adjusting the Mn2+ content in the electrolyte, the cell recovered its charging ability through electrodeposition of MnO2. Additionally, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 44 publications
(42 reference statements)
5
54
0
Order By: Relevance
“…[21] Along with the consumption of H + , the locally generated OH − can induce a pH-dependent conversion reaction with ZnSO 4 and H 2 O to form micrometer-scaled flake-like ZHS with 2D layered structure on its surface. [18,25,33,58,69,70] A further discharging degree to No. 6-1.00 V (fully discharged state) gives significant rises to the intensity of the peak ≈12°.…”
Section: Resultsmentioning
confidence: 99%
“…[21] Along with the consumption of H + , the locally generated OH − can induce a pH-dependent conversion reaction with ZnSO 4 and H 2 O to form micrometer-scaled flake-like ZHS with 2D layered structure on its surface. [18,25,33,58,69,70] A further discharging degree to No. 6-1.00 V (fully discharged state) gives significant rises to the intensity of the peak ≈12°.…”
Section: Resultsmentioning
confidence: 99%
“…Small 2021, 17, 2101515 reservoir for MnO 2 electrodeposition during charging. [12,29,33] This is the principle of a conversion battery, where finally the capacity of the electrolyte has to be taken into account for the energy density calculation. Some publications report on lower oxidation state manganese oxide cathode materials (i.e., spinel Mn 3 O 4 and MnO) capable of cycling in highly concentrated Al(OTf ) 3 aqueous electrolytes, free of Mn 2+ ions.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited pH increase occurring at the metal oxide/ electrolyte interface during the discharge (i.e., a local pH estimated to be 3 as discussed above), no precipitation of Al 3+based hydroxides/oxides is observed in our spectroelectrochemical experiments, in contrast to what is reported in Zn 2+ -based aqueous electrolytes. [28][29][30]…”
Section: In Operando Spectroelectrochemical Analysis Of the Charge Storage Mechanismmentioning
confidence: 99%
“…Because relying on protoncoupled electron transfers, this reaction is associated with significant local pH gradients, triggering precipitation of zinc hydroxides and restricting the gravimetric capacity, as well as to potential drifts. [10][11][12][13] To overcome these limitations, Mateos et al demonstrated the benefit of using a buffered aqueous electrolyte (pH = 5) to fully convert MnO 2 to water-soluble Mn 2+ (aq) at stable potential values and with low hysteresis through the highly reversible proton-coupled reaction given below: where AH and A are the weak Brønsted acid and base of the buffer, respectively. When performed on transparent 2D ITO electrodes, accumulation of an electrochemically inactive fraction of MnO 2 (ca.…”
Section: -3mentioning
confidence: 99%